Effect of Photoprotective Cream of Mangosteen Pericarp Extract (Garcinia Mongostana L) Against 8-OHdG After UVB Exposure On Albino Mice - Dian Amelia Abdi; Nasrum Massi; Khairuddin Djawad; Sri Vitayani; Nesyana Nurmadilla (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This study aims to determine the effect of the application of mangosteen pericarp extract cream(Garcinia Mangostana L) on levels of 8-OHdG on the skin of mice after exposure to UVB.Method: The study use a pure animal experimental research design with control group. The criteria forinclution were species Swiss albino mice, aged 6 – 9 weeks, weight 20-30 g, female gender and healthy.. Thesamples that met the criteria were divided into 5 groups : UVB, Base Cream plus UVB, 3 groups mangosteenpericarp extract cream with different concentration UVB radiation in mice using a 311 nm narrowband UVB(Dermalight 1000) with the power 450 mJ/cm three times a week for 4 week. Elisa examination was carriedout before and after the experiment.Result: This study used 25 mice albino selected randomly and were divided into 5 treatment groupconsisting of 5 group : UVB alone, UVB with base cream, UVB with mangosten pericarp extract cream withconcentration of 1 %, 3 % and 5 %. The Comperative test levels of 8-OhdG between each group with PostHoc test and found It was concluded that the decrease in OhdG was greatest in group 2 followed by groups5, 4, 3, and 1 (control group), respectively.Conclution: The ELISA levels of 8-OHdG was found that there are significant difference as between thevarious treatment groups (p>0,05). However, the increasing concentration of mangosten pericarp extractcream showed decreased level of 8-OHdG.